Polymer-Bioactive Glass Composite Filaments for 3D Scaffold Manufacturing by Fused Deposition Modeling: Fabrication and Characterization - Distler, Thomas; Fournier, Niklas; Grünewald, Alina; Polley, Christian; Seitz, Hermann; Detsch, Rainer; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2020)
Critical size bone defects are regularly treated by auto- and allograft transplantation. However, such treatments require to harvest bone from patient donor sites, with often limited tissue availability or risk of donor site morbidity. Not requiring bone donation, three-dimensionally (3D) printed implants and biomaterial-based tissue engineering (TE) strategies promise to be the next generation therapies for bone regeneration. We present here polylactic acid (PLA)-bioactive glass (BG) composite scaffolds manufactured by fused deposition modeling (FDM), involving the fabrication of PLA-BG composite filaments which are used to 3D print controlled open-porous and osteoinductive scaffolds. We demonstrated the printability of PLA-BG filaments as well as the bioactivity and cytocompatibility of PLA-BG scaffolds using pre-osteoblast MC3T3E1 cells. Gene expression analyses indicated the beneficial impact of BG inclusions in FDM scaffolds regarding osteoinduction, as BG inclusions lead to increased osteogenic differentiation of human adipose-derived stem cells in comparison to pristine PLA. Our findings confirm that FDM is a convenient additive manufacturing technology to develop PLA-BG composite scaffolds suitable for bone tissue engineering.
CRIS-Team Scopus Importer:2020-07-17
Keywords: 3D printing; 3D printing filaments; bioactive glass; bone tissue engineering; fused deposition modeling; polymer ceramic composites